Running of the number of degrees of freedom in quantum conformal gravity - Stefano Giaccari; Petr Jizba; Jaroslav Kňap; Lesław Rachwał (European Physical Journal C: Particles and Fields, 2024)
Abstract We study how the number of degrees of freedom in Weyl conformal gravity runs with the energy scale from the UV fixed point. To this end we employ two approaches. First, we utilize the Fradkin–Tseytlin prescription for the number of degrees of freedom and demonstrate that the one-loop result is highly dependent on the selected background. We then employ the counting methodology based on the a- and c-function, which are typically used to characterize the trace anomaly of conformal field theories in four dimensions. We compute these in the enhanced one-loop approximation and demonstrate that the degrees of freedom decrease monotonically from six degrees in the UV regime. This behavior is independent of the backgrounds considered. Further salient issues, such as the connection between the Fradkin–Tseytlin prescription and counting based on the a- and c-function, or the applicability of both methods in Einstein’s gravity, are also addressed.